Ecological plant breeding: types and practice - V. V. Syukov; V. G. Zakharov; A. I. Menibaev (Вавиловский журнал генетики и селекции)
The article describes the theoretical basis of ecological breeding. A critical analysis of the definition of this term and the theoretical foundations of ecological breeding, as a method of selection of genotype-environmental hereditary factors are presented. Two main types of the organization of ecological breeding are in focus: shuttle breeding actualized in CIMMYT and the All-Russian Research Institute of Vegetable Breeding and Seed Production (VNIISSOK), and conjugate breeding developed under such programs as “Ekada”, “Clover”, “Lucerne” and “Arid cultures”. The methodological approaches used in conjugate breeding are described in details. It is illustrated that ecological breeding can be represented by three modules: the formation of an artificial ecological gradient (ecological vector), the actual selection of genotypes with a wide norm of reaction (selection for homeoadaptability) and the organization of movement of the breeding material along the ecological vector. The practical implementation of ecological selection of the “conjugate selection” type was shown with the “Ekada” program as an example. The ecological vector of the program consists of six points arranged in historical breeding centers of the Volga-Ural region characterized by varying strength of factors that limit the growth and development of plants. The organizational scheme of selection lies in parallel testing pooled breeding material at all points of the ecological vector and isolating the most compliant lines. In this case, information, not genotypes, is what is transferred along the ecological gradient, in contrast to “shuttle selection”. The result of the work of the creative team “Ekada” was the development of series of spring wheat strains (e.g. Ekada 6, Ekada 70, Ekada 66, Ekada 109, Ekada 113), which were recommended for use in agricultural production.